Activation of P2X7 Receptors in Peritoneal and Meningeal Mast Cells Detected by Uptake of Organic Dyes: Possible Purinergic Triggers of Neuroinflammation in Meninges - Nurkhametova, Dilyara; Kudryavtsev, Igor; Guselnikova, Valeriia; Serebryakova, Maria; Giniatullina, Raisa R.; Wojciechowski, Sara; Tore, Fatma; Rizvanov, Albert; Koistinaho, Jari; Malm, Tarja; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2019)
Extracellular ATP activates inflammasome and triggers the release of multiple cytokines in various immune cells, a process primarily mediated by P2X7 receptors. However, the expression and functional properties of P2X7 receptors in native mast cells in tissues such as meninges where migraine pain originates from have not been explored. Here we report a novel model of murine cultured meningeal mast cells and using these, as well as easily accessible peritoneal mast cells, studied the mechanisms of ATP-mediated mast cell activation. We show that ATP induced a time and dose-dependent activation of peritoneal mast cells as analysed by the uptake of organic dye YO-PRO1 as well as DAPI. Both YO-PRO1 and DAPI uptake in mast cells was mediated by the P2X7 subtype of ATP receptors as demonstrated by the inhibitory effect of P2X7 antagonist A839977. Consistent with this, significant YO-PRO1 uptake was promoted by the P2X7 agonist BzATP. Extracellular ATP-induced degranulation of native and cultured meningeal mast cells was shown with Toluidine Blue staining. Taken together, these data demonstrate the important contribution of P2X7 receptors to ATP-driven activation of mast cells, suggesting these purinergic mechanisms as potential triggers of neuroinflammation and pain sensitization in migraine.